Complement's hidden arsenal: New insights and novel functions inside the cell. (April 2017) - Liszewski, M. Kathryn; Elvington, Michelle; Kulkarni, Hrishikesh S.; Atkinson, John P.
Highlights: New studies have demonstrated major new intracellular roles for complement: C3 is a damage-associated molecular pattern that can enhance intracellular innate immunity and help control cell survival. A C3(H2 O) recycling pathway is a component of the intracellular complement system. Autocrine activation of CD46 via T-cell derived C3b plays a key role in nutrient uptake and cellular metabolism. C3 activation fragments and factor H act as chaperones for the processing of apoptotic cargo. Intracellular C5 activation is essential for NLRP3 inflammasome assembly in CD4 + T cells. The full importance and mechanisms of complement's hidden intracellular arsenal continue to be elucidated. Other intracellular players including the C3a receptor (C3aR), the C5a receptor (C5aR), and factor B (FB) also are currently being evaluated. These new roles also suggest new therapeutic approaches. Abstract: A key component of both innate and adaptive immunity, new understandings of the complement system are expanding its roles beyond that traditionally appreciated. Evidence is accumulating that complement has an intracellular arsenal of components that provide not only immune defense, but also assist in key interactions for host cell functions. Although early work has primarily centered on T cells, the intracellular complement system likely functions in many if not most cells of the body. Some of these functions may trace their origins to the primitive complement system that began as a primeval form of C3 likely tasked for protection from intracellular pathogen invasion. This later expanded to include extracellular defense as C3 became a secreted protein to patrol the vasculature. Other components were added to the growing system including regulators to protect host cells from the indiscriminate effects of this potent system. Contemporary cells may retain some of these vestigial remnants. We now know that a) C3 serves as a damage-associated molecular pattern (in particular by coating pathogens that translocate into cells), b) most cells store C3 and recycle C3(H2 O) for immediate use, and c) C3 assists in cellular survival and metabolic reprogramming. Other components also are part of this hidden arsenal including C5, properdin, factors H and B, and complement receptors. Importantly, better definition of the intracellular complement system may translate into new target discovery to assist in creating the next generation of complement therapeutics.